Using Positive Deviance as an Approach in Action Research to Optimize Parental Learning Assistance for Children with Disabilities - Wiwin Hendriani (Indonesian Journal of Disability Studies, 2024)
The aim of this research is to assist parents of children with disabilities in optimizing the learning support they provide by leveraging the knowledge and experiences of those who have successfully improved their children's learning outcomes. The positive deviance methodology was selected for its ability to facilitate the transfer of effective strategies among participants. This methodology was employed as an action research approach, with each step focused on finding solutions to the identified problems. The study involved 20 parents of children with intellectual disabilities and autism spectrum disorder residing in Sidoarjo. Qualitative data were collected through interviews, focus group discussions, observations, and parents’ activity documentation submitted via Google Forms. Thematic analysis was used to analyze the data. The research identified several strategies to enhance parental learning assistance for children with disabilities by first identifying common challenges faced by these parents. Additionally, the study demonstrates that the positive deviance approach is applicable to any community, encouraging other communities to explore various potential solutions in the face of adversity without relying on external assistance.